Legal Liability from a Threefold Perspective. General Aspects: Array - Marin, Andrada-Georgiana (Journal of Danubian Studies and Research, 2021)
This paper aims at approaching general issues regarding the legal liability, starting from the principle of responsibility in the field of General Theory of Law to the legal liability under national law, public international law and European Union law. Legal liability under national law does not exhaust the subject, as the liability of states can be engaged at the level of international society – Draft articles of 2001 prepared by the International Law Commission within the United Nations, but also the liability of intergovernmental organizations – Draft articles of 2011. A controversial aspect, both at the normative level and at the doctrinal level, remains the international legal liability of the individual – natural person. The legal liability under the European Union law falls mainly to the states for the failure to fulfil their obligations according to the Union law, by means of the infringement procedure, other types of legal liability existing also at the level of the Union. In order to strengthen the concept of legal liability, in the light of the aspects promoted by the European Union, a special role was played by the European Commission, whose main mission was to ensure the application of and compliance with the European Union law, and the Court of Justice of the European Union by its extensive case-law.